Challenges during conservation works on heritage building / Muhammad Amzar Abu Bakar and Amir Fasha Mohd Isa - Abu Bakar, Muhammad Amzar; Mohd Isa, Amir Fasha (2023)
This research paper focuses on the challenges faced during conservation works on heritage buildings and provides recommendations to overcome these challenges. The study includes a literature review, interviews, and surveys to gather data on the various factors affecting conservation efforts. Refer to respective objectives of this research paper which is; to identify the challenges faced during conservation works of heritage buildings and to determine the procedure or method to encounter the challenges, the findings reveal that on-site challenges, economic and finance factors, organizational issues, human factors, and others are the main challenges encountered in heritage building conservation. The data analysis shows that decision-making regarding conservation activities, finding appropriate materials, and effective communication among professionals are the most challenging factors in their respective categories. Based on these findings, recommendations are made to prioritize effective communication, develop clear procedures to address challenges, manage and coordinate stakeholders, address human factor challenges, and address economic and finance challenges. Implementing these recommendations can improve the conservation process and ensure successful outcomes in heritage building conservation projects.